The lumbar arteries and veins: Quantification of variable anatomical positioning with application to retroperitoneal surgery. Issue 5 (2nd February 2015) - Beveridge, Tyler S.; Power, Adam; Johnson, Marjorie; Power, Nicholas E.; Allman, Brian L.
<x xml:space="preserve">Abstract</x> The lumbar arteries and veins are segmentally arranged vessels in the abdomen that supply the vertebrae and posterior abdominal/paravertebral muscles. Recent studies have indicated that these vessels have a tendency to vary from the classical description of bilateral pairing. The objective of this study was to more accurately characterize the anatomy of the lumbar vessels through the dissection of 22 cadaveric specimens and examination of 41 patients' computed tomography angiography scans. The positions of the lumbar vessels were measured in reference to the bifurcation/confluence of the common iliac arteries/veins. In 22 cadaveric specimens, the course of the lumbar veins was dissected to the psoas major muscle to characterize venous tributaries. Our results indicate that the lumbar veins were rarely paired, segmentally diverged closer to the iliocaval confluence, and preferentially drained into the left side of the IVC. Several types of lumbar veins were additionally characterized based on their consistent coursing patterns. In contrast, the lumbar arteries exhibited pairing, and these successive pairs were found to be equally spaced along the length of the infrarenal abdominal aorta. In specimens where the median sacral artery and 4th lumbar artery pair arose from a trifurcating common trunk, the positions of the 3rd and 4th lumbar arteries were significantly inferior (P < 0.05) compared to those with independent median sacral arteries. Clinically, proper management of the anatomical patterns described in this study may be pivotal in reducing the incidence of intraoperative damage to the lumbar vessels, and may help in the treatment of vascular diseases. Clin. Anat. 28:649–660, 2015. © 2015 Wiley Periodicals, Inc.